Modeling of building frames as spatial rod structures with geometric and physical nonlinearities - Vetyukov, Yuriy Mikhailovich; Eliseev, Vladimir Vasil'evich (Computational Continuum Mechanics, 2010)
We consider the stress-strain state of steel concrete rods, which comprise the frames of high multi-storey buildings under various static loadings: weight, wind, etc. The emphasis is put on geometric and physical nonlinearities in three-dimensional problems for the systems of multiple rods. Investigation is performed using the nonlinear theory of rods, physically nonlinear three-dimensional continuum mechanics in application to steel concrete, and the algorithms of computational mechanics.